(untitled) (JURNAL ADMINISTRASI PUBLIK, 2019)
The purpose of this study was to determine the accountability for the use of Village Funds in the South Karatung Village, Manusa District, Talaud Islands Regency. This research uses a descriptive qualitative approach. Accountability for the use of Village Funds can be seen from three dimensions of public accountability, namely financial accountability, benefit/effectiveness accountability, and procedural accountability. The research informants were the village head, village secretary, village treasurer, BPD chair, LPMD chair, and several figures and residents of South Karatung Village. Data collection uses interview guidelines, while the analysis technique used is an interactive model analysis from Miles and Hubernann. The results of the study show: (1) Financial Accountability is good enough, that is the received Village Funds are announced or informed transparently to the general public; its use planning involves the BPD and LPM, as well as elements of community representatives, and the results of the implementation are accounted for in a transparent manner by the authorities and informed to the wider community. (2) Accountability Benefits / Effectiveness is quite good, namely: the program is planned/determined according to the needs of the village community; the benefits can be felt by the community in terms of improving public services and in improving the standard of living and welfare of the community. (3) Procedural accountability is good enough, i.e. program planning is determined through village deliberations involving all relevant elements in the community; program/activity implementation procedures in accordance with the implementation instructions and technical management guidelines; and reporting and accountability mechanisms are carried out properly in accordance with village financial management guidelines. Keywords: Accountability, Village Funds.